The effectiveness of interventions on nutrition social behaviour change communication in improving child nutritional status within the first 1000 days: Evidence from a systematic review and meta‐analysis - Rashidul A. Mahumud *; Sophiya Uprety *; Nidhi Wali; Andre M. N. Renzaho; Stanley Chitekwe (Wiley, 2022)
Abstract This systematic review and meta‐analysis aimed to assess the robustness of designs and tools used in nutrition social behaviour change communication (NSBCC) interventions and establish their effectiveness. EBSCOhost as an umbrella database including Medline (Ovid) and CINAHL, EMBASE, and ProQUEST databases were searched for peer‐reviewed articles from January 1960 to October 2018. Additional sources were searched to identify all relevant studies including grey literature. Studies' biases were assessed according to Cochrane handbook. Pooled estimate of effectiveness of interventions on infant and young child feeding (IYCF) practices and child nutritional status with 95% confidence intervals were measured using random‐effects models. Eighty studies were included in this review: Fifty‐one (64%) were cluster randomised controlled trials (RCTs), 13 (16%) were RCTs and 16 (20%) quasi‐experimental. Of the included studies, 22 (27%) measured early initiation of breastfeeding, 38 (47%) measured exclusive breastfeeding, 29 (36%) measured minimum dietary diversity, 21 (26%) measured minimum meal frequency, 26 (32%) measured height for age z‐scores (HAZ), 23 (29%) measured weight for height z‐scores (WHZ), 27 (34%) measured weight for age z‐scores (WAZ), 20 (25%) measured stunting, 14 (17%) measured wasting, and 11 (14%) measured underweight. The overall intervention's effect was significant for exclusive breastfeeding (EBF) (odds ratio = 1.73; 95% confidence interval [CI]: 1.35-2.11, p < 0.001), HAZ (standardized mean differences [SMD] = 0.19; 95% CI: 0.17-0.21; p < 0.001), WHZ (SMD = 0.02; 95% CI: 0.004-0.04; p < 0.001), and WAZ (SMD = 0.04; 95% CI: 0.02-0.06; p < 0.001). Evidence shows the effectiveness of NSBCC in improving EBF and child anthropometric outcomes. Further research should test the impact on child nutritional status with clearly specified and detailed NSBCC interventions.